A influ??ncia dos estilos de gerenciamento do patrocinador na prioriza????o de projetos de sistemas de informa????o - Rodrigues, Luciana Magalh??es Girardin Pimentel (2018)
Project portfolio management also involves the project prioritization phase. The projects are classified and prioritized based on a set of criteria at this stage, in order to not exceed the available resources. In this context, the sponsor takes part in the prioritization process of information systems projects as an active figure, being responsible for establishing the project's priority individually or by committee. The sponsor's way of acting, which may be related to his / her management style, may influence the project prioritization process depending on what is being addressed and the organizational context. Thus, this research aims to understand how the different management styles of the sponsor influence the prioritization of information system projects. To do so, this research adopts a qualitative descriptive exploratory approach, with interpretivist-constructivist orientation, in which the data collection will be done through interviews (11). The analysis process was handled by the coding technique and the process of constant comparison of the data, according to the guidelines of Grounded Theory. Atlas.ti software was used throughout the analysis process, where co-occurrence analysis and "Codes Primary Documents Table" were used. Regarding the results, a matrix was presented evidencing the influence of management styles in certain contexts of the project prioritization process. As contributions of this research, the emergence of the opportunistic management style, the relevance of the strategic alignment with the project prioritization process, and the prescription of the investment committee and the post-project implementation analysis.